Transformasi Digital dalam Pelayanan Administrasi Kependudukan di Kabupaten Tangerang - Marsudi Marsudi; Agung Setiawan; Khikmawanto Khikmawanto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Digital transformation is a shift from traditional (manual) working methods to more modern and efficient ways of utilizing technology. This study aims to describe the digital transformation process in population administration services and the supporting and inhibiting factors in Tangerang Regency. The research method uses a qualitative approach. There are three data collection types: observation, interviews, and documentation. While the data analysis used is interactive. The results of the study show that the implementation of digital transformation in population administration services in Tangerang Regency has had a positive impact, especially in accelerating and facilitating access to services. Despite facing challenges such as limited technology, digital literacy, and human resource readiness, the government has taken strategic steps to overcome them. Continued infrastructure support and education programs are the key to success.